Dysmicoccus brevipes (Cockerell) occurrence and infestation behaviour as influenced by farm type, cropping systems and soil management practices - Kabi, Samuel; Karungi, Jeninah; Sigsgaard, Lene; Ssebuliba, James M. (Ecosystems & Environment, 2016)
Occurrence of pineapple mealybug (Dysmicoccus brevipes) has been increasing at an alarming rate on pineapple in Uganda. The cause of the epidemic is unknown. This study was set out to establish whether prevailing cropping systems, production and management practices could provide an insight into the trend. A biological monitoring study that covered 150 pineapple farms was conducted in 2012 and 2013. Farms were categorised under organic and conventional systems. Mealybug population densities (mealybugs/plant) were recorded in relation to seed bed types, cropping system and soil management practices used on each farm. Mealybug population densities were lower in pineapple–banana intercrop system (27.8) than in a sole pineapple crop (81.8) across seasons. Earthed-up seed beds registered higher mealybug densities (84.1) than flat seed beds (31). Earthed-up seed beds created more favourable environment for mealybug multiplication than flat beds. Use of coffee husks as a soil fertility amendment promoted mealybug population build up (83.8) whereas fallowing had a reducing effect (22.7). More indepth studies on the role of soil moisture and soil cover in mealybug population build-up in pineapples are recommended.
Keywords: Conventional system; Earthing-up; Fallowing; Foliar fertilizers; Organic system; Pineapple–banana intercrop